Connectivity, sport events, and tourism development of Mandalika’s special economic zone: A perspective from big data cognitive analytics - Rezzy Eko Caraka; Irwanda Wisnu Wardhana; Yunho Kim; Anjar Dimara Sakti; Prana Ugiana Gio; Maengseok Noh; Bens Pardamean (Cogent Business & Management)
This study examines the interplay of air connectivity, sports events, infrastructures, and fiscal support during the period 2017 and 2022 in a designated area called Special Economic Zone in Mandalika, Lombok Island, West Nusa Tenggara to boost tourism development in Indonesia by utilizing big data cognitive analytics. We examine the tourism development impacted by the MotoGP event in 2022 and air connectivity. Further, this paper discusses the network connectivity of flights at Zainuddin Abdul Madjid International Airport during the COVID-19 Pandemic and the new normal. We found that the combination of an international airport, globally recognized sports events, and government support has directly and positively improved the tourism industry’s performance in the country and especially within Lombok Island. We suggest policy recommendations to support economic activities in Mandalika’s Special Economic Zone and its hinterland to maintain business sustainability and utilize the existing infrastructures at the optimum level. Lessons learned from the Indonesian experience could help other developing countries that are devising policies and strategies to develop the tourism industry by employing proper instruments such as infrastructure, events, and fiscal policies.